2022
DOI: 10.3390/polym14122494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyhydroxyalkanoate (PHA) Concentration on Polymeric Scaffolds Based on Blends of Poly-L-Lactic Acid (PLLA) and PHA Prepared via Thermally Induced Phase Separation (TIPS)

Abstract: Hybrid porous scaffolds composed of both natural and synthetic biopolymers have demonstrated significant improvements in the tissue engineering field. This study investigates for the first time the fabrication route and characterization of poly-L-lactic acid scaffolds blended with polyhydroxyalkanoate up to 30 wt%. The hybrid scaffolds were prepared by a thermally induced phase separation method starting from ternary solutions. The microstructure of the hybrid porous structures was analyzed by scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…These reports have further broadened current and perspective applications of PHAbased materials (Table 1). SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63]. SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These reports have further broadened current and perspective applications of PHAbased materials (Table 1). SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63]. SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63].…”
Section: Discussionmentioning
confidence: 93%
“…These reports have further broadened current and perspective applications of PHAbased materials (Table 1). SEM studies demonstrated significant variability on the nanolevel 3D structures of the ES mixtures P(3HB): mcl-PHA [62] and foams PLLA/PHA [63]. Studies have proven that combining different types of PHAs (see Figure 4) in right proportions with other material significantly enhances wide variety of their properties [60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the sake of brevity, FTIR-ATR spectra of P-PLA/Chi samples are not shown, as no significant differences were found in comparison with PLA/Chi results. According to the literature, the ATR-FTIR spectrum of PLA showed various absorption bands usually attributed to this polyester, such as the carbonyl stretch at 1747 cm −1 ; the C–O stretch at 1180 cm −1 , 1129 cm −1 and 1083 cm −1 ; and the OH bend at 1044 cm −1 [ 41 ]. The FTIR-ATR spectrum of neat chitosan powder reveals main absorption bands at 3352 cm (stretching vibration of O–H group) [ 42 ], 3290 cm −1 (stretching vibration of N–H) [ 42 ], 1645 cm −1 (stretching vibration of the carbonyl group (C=O) in amide I) [ 43 , 44 ], and 1039 cm −1 (stretch vibrations of C–O) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%